Soil risk maps – Interpreting soils data for policy makers, agencies and industry. (15th November 2019) - Baggaley, Nikki; Lilly, Allan; Blackstock, Kirsty; Dobbie, Karen; Carson, Adam; Leith, Fraser
Abstract: Surface runoff, erosion, compaction and the leaching of potential pollutants from land can degrade the soil resource and damage the water environment, reducing crop yields, causing loss of valuable nutrients and organic matter, together with increasing flood risk. Increasingly, it is recognized that scientific information must be translated into practical tools to change practices and protect the soil and water resource. Working alongside agencies in Scotland, we applied a suite of simple, transparent, rule‐based models to identify areas most at risk of exporting sediment and pollutants that may degrade water quality based on field‐scale (1:25, 000) soil maps. The maps have been used by Scottish Environment Protection Agency, Scottish Water and Scottish Government to assess soil risks to waters from field to regional scale. The work brought scientists together with policy makers, agencies and the water industry to pool their knowledge to apply these practical tools for decision‐making. It highlights the need to apply existing knowledge to answer salient questions. All three examples described show that providing the right type of information, which is based on fundamental soils data, can directly influence the implementation of policies, investment and monitoring decisions and provide evidence in support of government. However, this requires both researchers and agency scientists to develop skills as knowledge brokers and to normalize the use of soil data in everyday agency settings.